PENGARUH MOTIVASI, SUMBER DANA, TEKNOLOGI DAN AKSES INFORMASI, STRATEGI PASAR, SERTA ENTREPRENEUR SKILLTERHADAP PERKEMBANGAN UMKM PEREMPUAN DI KOTA PALEMBANG - Lisnini - Lisnini; Fetty - Maretha; Yulia - Pebrianti; Rini - Rini (Politeknik Negeri Semarang, 2018)
This research is aimed to test the effect of motivation, source of funds, tecnology and information access, market strategy, and entrepreneur skill on the small and medium enterprises development. The research uses a data set consist of 325 small and medium women enterprises unit with 100 respondents.Regression analysis is used to compute the parameters. The results show that there are correlations between Motivation, source of funds,technology and information access, marketing strategy, and entrepreneur skill with enterprises development.Motivation has significant effect on the small and medium enterprises development. Source of funds, technology and information access, marketing strategy, and entrepreneur skill has no significant effect on the small and medium enterprises development.